Qualitative variability of dissolved organic matter in the Baltic Sea sediments apparent from fluxes and optical properties - Loginova, Alexandra N.; Wünsch, Urban J.; Zabłocka, Monika; Cherkasheva, Aleksandra; Szymczycha, Beata; Kuliński, Karol; Winogradow, Aleksandra; Kowalczuk, Piotr (Frontiers in Marine Science, 2024)
The release of dissolved organic matter (DOM) from sediments serves as an important part of the carbon cycle. Here, we address pore water DOM quality and its release from shallow sediments (0–10 cm) of the central and southern Baltic Sea - Gdansk, Bornholm, and Eastern Gotland Basins - using excitation–emission matrix spectroscopy and size-exclusion chromatography. DOM release from sediments displayed spatial variability, with diffusive DOC fluxes ranging from 0.02 to 1.06 mmol m−2 d−1, and basin-averaged fluxes increased in the order Gotland < Bornholm < Gdansk. DOM qualitative characteristics also varied among investigated basins. In the oxygen-limited study sites from the Gdansk Basin, we observed elevated abundances of low apparent molecular weight DOM fraction and proteinaceous-like fluorescent DOM, while in the Bornholm Basin, pore water DOM was generally more humic-like and of higher apparent molecular weight. Pore waters from the deepest study sites in the Gotland Basin were qualitatively very similar to those of the pore waters from the upper sediment layers (0–4 cm) from all other investigated sites, suggesting little organic matter reworking at depth at those stations. Our results suggest that the spatial variability in the magnitude of DOM release may be linked to the qualitative differences of DOM in sediments.